2021
DOI: 10.1016/j.htct.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status at diagnosis among children with cancer referred to a nutritional service in Brazil

Abstract: Introduction Children and adolescents with cancer are particularly vulnerable to malnutrition and require special attention on nutritional assessment. An adequate nutritional status during treatment is essential in reducing morbidity and mortality, being a modifiable risk factor for clinical outcomes. This study aims to determine the nutritional status of pediatric patients with cancer assessed by the nutrition team at diagnosis and evaluate its association with the overall survival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 24 publications
1
15
1
1
Order By: Relevance
“…About 34.2% of pediatric patients with cancer at diagnosis had undernutrition and malnutrition in Brazil. These findings could indicate patients who are at a high nutritional risk as a result of reduced dietary intake and symptoms like nausea and vomiting, which can cause significant weight loss before diagnosis 37 . Previous research indicated moderate–severe malnutrition during treatment as predictors with HR 2.06 (95% CI: 1.06–4.01) and 3.5 (95% CI: 2.11–5.81), respectively 28 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…About 34.2% of pediatric patients with cancer at diagnosis had undernutrition and malnutrition in Brazil. These findings could indicate patients who are at a high nutritional risk as a result of reduced dietary intake and symptoms like nausea and vomiting, which can cause significant weight loss before diagnosis 37 . Previous research indicated moderate–severe malnutrition during treatment as predictors with HR 2.06 (95% CI: 1.06–4.01) and 3.5 (95% CI: 2.11–5.81), respectively 28 .…”
Section: Discussionmentioning
confidence: 87%
“…These findings could indicate patients who are at a high nutritional risk as a result of reduced dietary intake and symptoms like nausea and vomiting, which can cause significant weight loss before diagnosis. 37 Previous research indicated moderate-severe malnutrition during treatment as predictors with HR 2.06 (95% CI:…”
Section: Duration Of Treatment (Months)mentioning
confidence: 98%
“…26 T A B L E 2 (a) Model Other studies investigating altered nutritional status in children with cancer in Brazil have not found an association between malnutrition and survival. 14,27 For example, in a study in Southeast Brazil, Viani et al 14 did not find an association between malnutrition at the time of diagnosis, assessed by BMI/A, AP, and overall survival in children with cancer. Similar findings were described by Pedrosa et al 27 in a study in Northeastern Brazil, who also did not find an association between malnutrition (classified by weight for height) at the time of diagnosis and overall survival in paediatric patients with cancer.…”
Section: Discussionmentioning
confidence: 97%
“…Na criança com câncer, a incidência de desnutrição varia muito durante o tratamento, pois depende do tipo de neoplasia e modalidade de intervenção, sendo relatada entre 0% e 70% 24 . No Brasil, a prevalência de desnutrição no câncer pediátrico é de 6% a 25% no momento do diagnóstico 25,26 , bem superior à média de desnutrição da população brasileira infantil. O sobrepeso e a obesidade também estão presentes nas crianças e adolescente com câncer ao diagnóstico, com prevalência em torno de em 8,6% a 14,8% 9 .…”
Section: Discussionunclassified